In Situ Bioremediation Techniques to Reduce Total Organic Matter Oversaturation of Fluvial Sediments: An Experimental Study - Carlos Rochera; Antonio Picazo; Nayeli Murueta; Antonio Camacho (Applied Sciences, 2020)
An in situ experiment was performed in sediments of River Magro (east Spain) in order to evaluate the usefulness of microbial bioremediation, both bioaugmentation and biostimulation, as a tool for reducing the excessive organic matter (OM) content in dammed river stretches due to historical wastewater spilling. The study had a prospective approach focused on the application of a biologically active commercial product (BAP), consisting of a mix of bacterial strains, ectoenzymes, and nutrients, where a range of concentrations and temporal dosages of the product were experimentally assayed in situ. They were further combined with the addition of potential organic enhancers, such as acetate, as well as of inhibitors of specific microbial guilds. On the other hand, inorganic electron acceptors for the anaerobic respiration of the organic matter were additionally amended. In additional assays, the BAP additions were combined with inorganic nutrients amendments, or even the latter were tested alone. These combinative treatments aimed at exploring the possible enhancement of synergistic or antagonistic interactions among the amended compounds, as well as the eventual effect of growth limiting factors. The single BAP additions of 50 g/m3 led to OM reductions of up to 17%, and significant removals of nitrogen or phosphorus were additionally observed by increasing or by fractioning the BAP dosage, respectively. However, a better response using the same amount of the BAP was obtained by supplementing it with sodium acetate. In this case, reductions of the OM content reached up to 35% of the accumulated OM, thus indicating that a complementary stimulus is still necessary to run out barriers towards the final steps of the anaerobic OM digestion. This treatment was also linked to the strongest significant drop in the TP content of the sediments. Neither the addition of inorganic electron acceptors nor inorganic nutrients improved the results, or they were even antagonistic of the degradative potential of the BAP product. Apparently, the occurrence of acetoclastic microorganisms, which was demonstrated by high throughput DNA-sequencing, was critical for the optimal OM reductions in the sediments. This exploratory study demonstrates that the applicability of BAPs can be extended to cover the remediation of fluvial ecosystems, and support the complementarity of different bioremediation strategies.